PENGARUH MEDIA GAMBAR SERI TERHADAP MINAT MENULIS DAN KETERAMPILAN MENULIS NARASI SISWA KELAS V DI SEKOLAH DASAR - Rahmita Galuh Maulidia; Laelia Nurpratiwiningsih; Rila Melyana Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of serial picture media on students’ writing interest and narrative writing skills in grade V of elementary school. This research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The participants were 44 students, consisting 20 students in the experimental school calss at SD Negeri Pemaron 01 Brebes and 24 students in the control class at SD Negeri Pemaron 03 Brebes. Data were collected through a writing interest questionnaire, a narrative writing test, and documentation. The data were analyzed using MANOVA after meeting the assumptions of normality, hoogenity, and Box’s M tests. The results showed that serial picture media had a significant effect on students’ writing interes and narrative writing skills. The MANOVA test obtained a significance value of 0.000 < 0.05, indicating a simultaneous effect on both variables. Serial picture media helped students generate ideas, understand event sequences, and compose narrative more coherently